2021
DOI: 10.1155/2021/9698371
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multiband Remote-Sensing Image Encryption Algorithm Based on Dual-Channel Key Transmission Model

Abstract: With the rapid development of remote sensing technology, satellite remote sensing images have been involved in many areas of people’s lives. Remote sensing images contain military secrets, land profiles, and other sensitive data, so it is urgent to encrypt remote sensing images. This paper proposes a dual-channel key transmission model. The plaintext related key is embedded into the ciphertext image through bit-level key hiding transmission strategy, which enhanced the ability of ciphertext image to resist kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The information entropy for numerous encrypted images was computed in this paper, and the results, as outlined in table 5, demonstrate that the entropies of all encrypted images closely approximate 8. Therefore, it can be concluded that our scheme has an average entropy of 7.9997 and is superior to the schemes in [28][29][30][31][32].…”
Section: Information Entropy Analysismentioning
confidence: 79%
“…The information entropy for numerous encrypted images was computed in this paper, and the results, as outlined in table 5, demonstrate that the entropies of all encrypted images closely approximate 8. Therefore, it can be concluded that our scheme has an average entropy of 7.9997 and is superior to the schemes in [28][29][30][31][32].…”
Section: Information Entropy Analysismentioning
confidence: 79%
“…[1] Since the 1920s, remote sensing has been employed in diverse military applications, including target detection, positioning and intelligence gathering. [2] With the advent of new data acquisition platforms, spectrum sensors can now be deployed on smaller platforms such as robots and unmanned aerial vehicles (UAVs). The remarkable mobility and cost-effectiveness of these new platforms make them an optimal choice.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the image encryption algorithm includes scrambling and diffusion. In order to obtain better an encryption effect, most of the existing image encryption schemes are organically combined with DNA coding [ 5 ], S-box transformation [ 6 ], compressed sensing, bit level [ 7 ], semi-tensor product operation [ 8 , 9 ], fractal model [ 10 ], and other advanced technologies. Ayubi et al.…”
Section: Introductionmentioning
confidence: 99%